2015
DOI: 10.1111/jog.12795
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of fetal anteroposterior to transverse cerebellar diameter for detection of the cerebellar hypoplasia in the second trimester and comparison with trisomy 18

Abstract: This study showed that not only TCD but also APCD correlated with gestational age, and APCD/TCD ratio indicated a fixed value (almost 0.5) in normal fetuses. Furthermore, APCD and APCD/TCD ratio were deemed useful indicators for cerebellar hypoplasia. In particular, the APCD/TCD ratio proved more convenient, without requiring individual evaluation of TCD and APCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Ultrasound examinations were performed using an ARIETTA 60 or 70 ultrasound machine (Hitachi, Ltd.) and a GE Voluson E8 ultrasound machine (GE Healthcare UK Ltd.). Fetal TCD and APCD were measured as previously described . In brief, we identified the cerebellar hemispheres in the posterior fossa of the plane that was obtained by slightly rotating the transducer below the thalamic plane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasound examinations were performed using an ARIETTA 60 or 70 ultrasound machine (Hitachi, Ltd.) and a GE Voluson E8 ultrasound machine (GE Healthcare UK Ltd.). Fetal TCD and APCD were measured as previously described . In brief, we identified the cerebellar hemispheres in the posterior fossa of the plane that was obtained by slightly rotating the transducer below the thalamic plane.…”
Section: Methodsmentioning
confidence: 99%
“…A small transverse cerebellar diameter (TCD) and enlarged cisterna magna have been reported in trisomy 18, but evaluation of these areas, particularly in the early second trimester, is often normal. Our previous study and a study by Hayata et al . both showed that a small anteroposterior cerebellar diameter (APCD) is a complication of trisomy 18.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Starting at 28 weeks of gestation, the references deviate from each other, e. g. the TCD in the third trimester is larger according to Verburg than according to Snijders and Goldstein [16]. Other standards for size parameters are published: ratio of anteroposterior (AP) to transverse cerebellar diameter [21], circumference and area of the cerebellar hemispheres [22].…”
Section: Transcerebellar Diameter (Tcd)mentioning
confidence: 99%
“…However, CH was the most severe in trisomy 18 than in trisomy 21 and 13 . Anteroposterior cerebellum diameter (APCD) and APCD to transverse cerebellum diameter (TCD) ratio seemed more remarkable and effective for CH than TCD . The aim of this study is to compare CSP/APCD and APCD/TCD ratios in normal fetuses with those in aneuploid fetuses, and to propose a new, simple ratio, CSP/APCD ratio for the identification of fetuses suspected of trisomy 18, and to validate the APCD/TCD ratio which had been studied.…”
Section: Introductionmentioning
confidence: 99%